2022
DOI: 10.1371/journal.pone.0270057
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of association and distribution of estuarine-resident common bottlenose dolphins (Tursiops truncatus) in North Carolina, USA

Abstract: The social structure of estuarine-resident bottlenose dolphins is complex and varied. Residing in habitats often utilized for resource exploitation, dolphins are at risk due to anthropogenic pressures while still federally protected. Effective conservation is predicated upon accurate abundance estimates. In North Carolina, two estuarine-resident stocks (demographically independent groups) of common bottlenose dolphin have been designated using spatiotemporal criteria. Both stocks are subjected to bycatch in fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 112 publications
1
3
0
Order By: Relevance
“…Titcomb et al (2015) conducted a study on a population of estuarine bottlenose dolphins in the Indian River Lagoon, Florida, organized into 6 distinct social clusters. The same number of clusters ( n = 6) was reported by Hohn et al (2022) in North Carolina. Urian et al (2009) reported that dolphins in Tampa Bay, Florida formed 5 clusters.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Titcomb et al (2015) conducted a study on a population of estuarine bottlenose dolphins in the Indian River Lagoon, Florida, organized into 6 distinct social clusters. The same number of clusters ( n = 6) was reported by Hohn et al (2022) in North Carolina. Urian et al (2009) reported that dolphins in Tampa Bay, Florida formed 5 clusters.…”
Section: Discussionsupporting
confidence: 66%
“…Dolphins from SGES that comprised small clusters associated loosely with the large clusters, both according to the sociogram (Figure 4) and based on the social metric strength values measured between clusters (Table S2). A social network analysis of estuarine dolphins in North Carolina, USA, resulted in nearly identical delineations as the SGES stock where they reported 3 large clusters (23-35 individuals) and 3 small clusters (1-3 individuals; Hohn et al 2022). Differences observed among clusters, based on data from other populations, could be related to the physical environment and habitat complexity (Karczmarski et al 2005, Wiszniewski et al 2009), resource availability (Lusseau et al 2003), predation risk (Wilkinson et al 2017), foraging strategy (Torres and Read 2009), and possibly anthropogenic activities (Greenfield et al 2021).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations